If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -3k = -1 Solving 19 + -3k = -1 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -3k = -1 + -19 Combine like terms: 19 + -19 = 0 0 + -3k = -1 + -19 -3k = -1 + -19 Combine like terms: -1 + -19 = -20 -3k = -20 Divide each side by '-3'. k = 6.666666667 Simplifying k = 6.666666667
| 10=3u+6+7w+14 | | 11=-2m+1-4 | | 6y+5/4=7y+1/4 | | 4y-10+3x+9x+12=180 | | x^2+y^2-6x-16=0 | | 7=34(x+20) | | (1/63)-(1/9) | | 4(5x+2)+5(3x-5)= | | 18-2x=x+3 | | -1x=1.5 | | 2x-9y+7x-20y= | | 6+0.5y=2(3-1/4y) | | x-20+2x-45=2x-5 | | (5x+30)=(15x+65) | | -6x+4=5x-62 | | 7-a/4.2 | | x-5+3x+2=63-23 | | 3v-14=7 | | 7=4/3(x+15) | | 3(5x+1)+(3x+3)= | | 2x^2+5x+k=0 | | -8n+5(1+5n)=-6n-14 | | 0.25x+0.6=0.125x*2 | | 7 = 43(x+15) | | -4/5(x-5)=2/3(x-5) | | 9x=y+9 | | 48-6x=17 | | 19-2k=-1 | | 4(s+1)=8(s+3) | | -5(3x+3)-4(4x-1)= | | x=88-2(y-10) | | 5(x+5)/3=3x-2 |